Analysis of methods of testing cabins of grain harvesting combiners (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article examines and analyzes the existing methods of testing cabins for durability and methods of evaluating the visibility of cabins. The national standard of Ukraine DSTU ISO 5700:2004 establishes the static load test method and the conditions for acceptance of protective structures (cabins or frames) of wheeled combines for agriculture and forestry. The national standard of Ukraine DSTU ISO 3463:2015 establishes the method of dynamic testing, the conditions of acceptance of protective structures for protection during overturning (cabin or frame) of agricultural and forestry wheeled combines. Practical testing using various stands, taking into account the requirements of regulatory documents for the characteristics of the impact of testing equipment on the protective structure, allows you to check theoretical patterns, assess the compliance of the cabin design, establish the actual value of absorbed energy from the applied load, work out the stages of applying loads in practice and check the accuracy of the measurement system. Visibility from the operator's workplace" establishes requirements, test methods and acceptance criteria for the operator's visibility. The design and equipment of the harvester must ensure the appropriate visibility of the operator when driving on public roads and when performing fieldwork. Visibility is considered appropriate if the operator is provided with at least partial visibility of each front wheel or wing when moving in a straight line and with a track width that corresponds to the total width of the combine with single wheels no more than 2.55 m.
Keywords: protective structure; statistical load; dynamic load; visibility; testing